Synthetic aesthetics investigating synthetic biology's designs on nature - Ginsberg, Alexandra Daisy (Cambridge, Mass. MIT Press, 2014)
"Synthetic biology manipulates the stuff of life. For synthetic biologists, living matter is programmable material. In search of carbon-neutral fuels, sustainable manufacturing techniques, and innovative drugs, these researchers aim to redesign existing organisms and even construct completely novel biological entities. Some synthetic biologists see themselves as designers, inventing new products and applications. But if biology is viewed as a malleable, engineerable, designable medium, what is the role of design and how will its values apply? In this book, synthetic biologists, artists, designers, and social scientists investigate synthetic biology and design. After chapters that introduce the science and set the terms of the discussion, the book follows six boundary-crossing collaborations between artists and designers and synthetic biologists from around the world, helping us understand what it might mean to 'design nature.' These collaborations have resulted in biological computers that calculate form; speculative packaging that builds its own contents; algae that feeds on circuit boards; and a sampling of human cheeses. They raise intriguing questions about the scientific process, the delegation of creativity, our relationship to designed matter, and, the importance of critical engagement. Should these projects be considered art, design, synthetic biology, or something else altogether? Synthetic biology is driven by its potential; some of these projects are fictions, beyond the current capabilities of the technology. Yet even as fictions, they help illuminate, question, and even shape the future of the field." -- Publisher's description.
Synthetic biology : what it is and why it matters / Alistair Elfick and Drew Endy -- Countering the engineering mindset : the conflict of art and synthetic biology / Oron Catts and Ionat Zurr -- Design as the machines come to life / Alexandra Daisy Ginsberg -- Nature is designed / Drew Endy -- There is no design in nature / Pablo Schyfter -- Design evolution / Alexandra Daisy Ginsberg -- Bio logic / David Benjamin and Fernan Federici -- Scale and metaphor / Pablo Schyfter -- Living among living things / Will Carey ... [et al.] -- Constrained creativity : an engineer's perspective / Alistair Elfick -- The biogenic timestamp : exploring the rearrangement of matter through synthetic biology and art / Oron Catts and Hideo Iwasaki -- Time as critique / Jane Calvert -- Synthetic sound from synthetic biology / Chris Chafe and Mariana Leguia -- Abstraction and representation / Pablo Schyfter -- Living machines / Sheref Mansy and Sascha Pohflepp -- Evolution vs. design? / Jane Calvert -- The inside out body / Christina Agapakis and Sissel Tolaas -- Transgressing biological boundaries / Alexandra Daisy Ginsberg.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Art and biology; Synthetic biology